Exposure to a 0.9-GHz electromagnetic field on postnatal days 21–45 may trigger the renin-angiotensin system in male rat: a histological and biochemical study - Keleş, Ayşe İkinci; Kaya, Haydar; Keleş, Gökhan; Erol, Hüseyin Serkan; Mercantepe, Tolga; Odaci, Ersan (Springer Science and Business Media LLC, 2024)
Abstract
The aim of this study was to examine the relationship between the renin-angiotensin system (RAS) and histological and biochemical changes occurring in the kidney tissue of male rats exposed to a 0.9 Gigahertz electromagnetic field (EMF). Twelve male rats aged 21 days were randomly assigned to control (C-Gr) and EMF (EMF-Gr) groups. No procedure was performed on C-Gr, while the EMF-Gr rats were exposed to a 0.9 Gigahertz EMF on postnatal days 21–45 (one hour a day for 25 days). Tissues were removed at the end of the experiment and evaluated using biochemical, histopathological, and stereological methods. Increased kidney tissue volume and weight and total body weight were determined in the group exposed to EMF. Lipid peroxidation, glutathione, catalase, and superoxide dismutase also increased in the kidney tissue of the EMF-Gr rats. Histopathological evaluation revealed cortical/medullary bleeding/obstruction and widespread fibrosis, dilatation, vacuolization, and degeneration in distal and proximal tubules, decreased and atypical parietal cells, and degeneration in epithelial cells. Additionally, dilated and degenerated glomeruli in the Malpighian body, Bowman’s membrane degeneration and degeneration in the vascular pole, podocyte, pedicel and mesangial cells were also observed. As a result of exposure to EMF, oxidative stress, tissue volume and weight increased, and histopathological changes caused the formation of a pathway that triggers RAS in kidney tissues. In conclusion, long-term exposure to 0.9 GHz EMF can activate the renin-angiotensin system in the rat kidney, and we think that such activation may be associated with structural, histopathological, and biochemical changes occurring in renal tissue.
Keywords: Male; Superoxide Dismutase; Body Weight; Male Rat; Kidney; Catalase; Glutathione; Rats; Renin-Angiotensin System; Oxidative Stress; Electromagnetic Field; Electromagnetic Fields; Animals; Lipid Peroxidation; Renin-angiotensin System